International trade and economic growth : studies in pure theory - Johnson, Harry G. (London : Allen & Unwin, 1958)
The studies collected in this volume embody the results of research conducted during the past four years into various theoretical problems in international economics. They fall naturally into three groups- comparative cost theory, trade and growth, and balance of payments theory
Includes index
rpm 21/01/2019
Loans
Keywords: Commerce